The geotourist attractions in the vicinity of Szczawnica spa - Golonka, Jan; Waśkowska, Anna; Doktor, Marek; Krobicki, Michał; Słomka, Tadeusz (Geotourism/Geoturystyka, 2015)
The main aim of this paper is presentation of the most characteristic outcrops/geological monuments, which occur in Szczawnica spa vicinity and are perfect geotouristic objects. These objects are presented with short geological/geomorphological remarks about their origin, development and signifi cance in natural sciences. They provide the excellent inanimate natural monuments (geotourist trail in Pieniny Mountains from Szczawnica to Červený Kláštor, Palenica Mountain, Zawiasy area, Bryjarka Mountain, Jarmuta Mountain and Zaskalnik Waterfall), which can be used for better understanding of the history of our Earth and numerous geological processes, which „sculptured” its surface, especially very complicated geological story of the Pieniny Klippen Belt.